Environmental Impact Analysis on School Building Reconstruction (Case Study: SDN Sukatani 7, Depok City) - Alimuddin Alimuddin; Rulhendri Rulhendri; Nurul Chayati; Jafar Sidik (Journal of Applied Geospatial Information, 2020)
In order to improve educational facilities and infrastructure, Department of Housing and Settlements, Depok City plans to reconstruction a school building. With the impacts caused by this activity, an environmental impact assessment is needed. The purpose of this study is to obtain the results of an analysis of environmental impact studies and ways of mitigation in minimizing the impacts that occur during pre construction stage, construction stage, and operation stage. The method used is observation, interview and scoping methods to determine the impact and good handling of the environment. The results of this study are obtained an analysis of environmental impacts that occur during the activity and how to minimize the impacts with good handling in order to create an environmental friendly construction.